Evaluating the Effectiveness in Initiating Help-Seeking Behaviors by Exposure to an Adult Male Public Service Announcement. Issue 1 (2nd January 2022) - Reidenberg, Daniel; Berman, Alan
Abstract: Numerous studies have demonstrated that PSA campaigns can be effective in increasing awareness/knowledge, attitudes, intentions to change behaviors, and ultimately behaviors; and the majority of suicide prevention PSAs encourage help-seeking behavior by the person at-risk and/or by those worried about a person who might be at risk of suicide. However, to date, only a handful of studies have evaluated the impact of suicide prevention [PSA] campaigns and no suicide prevention PSA campaign has examined whether behavior change occurs in response to short-term implementation of a suicide prevention PSA. The primary goal of this study is to determine whether exposure to short-term (1 month) suicide prevention PSA campaign results in a help-seeking behavior. Results offer initial, limited evidence that public awareness campaigns are effective at getting an audience to engage in a help-seeking behavior, however due to methodological limitations, the superiority of a PSA vs. a printed flyer was not able to be determined.